Development of Monoclonal Antibodies against Ureaplasma urealyticum Serotypes and Their Use for Serotyping Clinical Isolates - Echahidi, Fedoua (American Society for Microbiology, 2000)
Monoclonal antibodies (MAbs) against Ureaplasma urealyticum serotype 2, 5, 7, 8, 10, 11, 12, and 13 reference strains were developed. The reactivities of these MAbs with the 14 serotype reference strains was verified by colony immunofluorescence assay and Western blot assay. MAbs against serotypes 2, 7, 10, 11, and 12 were serotype specific, whereas MAbs against serotypes 5, 8, and 13 showed cross-reactivity. All MAbs against serotype 5 were cross-reactive with serotype 2, and one showed, in addition, cross-reactivity to serotypes 9 and 10. Mutual cross-reactivities were observed between MAbs against serotypes 8 and 13. The usefulness of the MAbs for the serotyping of U. urealyticum strains was evaluated by serotyping 21 selected clinical isolates. A complete set of MAbs (the newly developed MAbs and the previously described MAbs against serotypes 1, 3, 4, 6, 9, and 14) as well as a complete set of polyclonal antibodies (PAbs), PAbs 1 to 14, were used. MAbs were able to identify 18 of 21 isolates including 2 isolates with mixed serotypes. Polyreactivity, which occurred with 19 of the 21 isolates with PAbs, was not observed by the use of MAbs. MAbs seem to be a more valuable tool than PAbs for serotyping and could help in investigating a possible link between the expression or variability of the serotype-specific antigens and pathogenicity.